A Systematic Review of Pedagogical Models to Enhance Students’ Critical Thinking in Physics Learning - Rasyid, Muhammad; Unayah, Habibatul; Kuswanto, Heru; Aminatun, Tien; Sulistiyawati, Sulistiyawati; Bog, Kim Jung (FKIP Universitas Lampung, 2024)
Critical thinking skills are important skills needed in the 21st century Critical thinking skills can be trained in students through student-centered learning This research aims to identify learning models that can improve physics critical thinking skills through a literature review Data collection is based on Scopus and SINTA database sources This type of document comes from magazine articles tagged